Mammographic density is the main correlate of tumors detected on ultrasound but not on mammography. Issue 9 (19th July 2016) - Häberle, Lothar; Fasching, Peter A.; Brehm, Barbara; Heusinger, Katharina; Jud, Sebastian M.; Loehberg, Christian R.; Hack, Carolin C.; Preuss, Caroline; Lux, Michael P.; Hartmann, Arndt; Vachon, Celine M.; Meier‐Meitinger, Martina; et al.
Abstract : Although mammography screening programs do not include ultrasound examinations, some diagnostic units do provide women with both mammography and ultrasonography. This article is concerned with estimating the risk of a breast cancer patient diagnosed in a hospital‐based mammography unit having a tumor that is visible on ultrasound but not on mammography. A total of 1, 399 women with invasive breast cancer from a hospital‐based diagnostic mammography unit were included in this retrospective study. For inclusion, mammograms from the time of the primary diagnosis had to be available for computer‐assisted assessment of percentage mammographic density (PMD), as well as Breast Imaging Reporting and Data System (BIRADS) assessment of mammography. In addition, ultrasound findings were available for the complete cohort as part of routine diagnostic procedures, regardless of any patient or imaging characteristics. Logistic regression analyses were conducted to identify predictors of mammography failure, defined as BIRADS assessment 1 or 2. The probability that the visibility of a tumor might be masked at diagnosis was estimated using a regression model with the identified predictors. Tumors were only visible on ultrasound in 107 cases (7.6%). PMD was the strongest predictor for mammography failure, but age, body mass index and previous breast surgery also influenced the risk, independently of the PMD. Risk probabilities ranged from 1% for a defined low‐risk group up to 40% for a high‐risk group. These findings might help identify women who should be offered ultrasound examinations in addition to mammography. Abstract : What's new? Invasive breast cancer presents as an uncalcified mass that appears dense on mammography, making detection more difficult in women with naturally dense breast tissue. Additional ultrasonography might increase sensitivity, but published studies only included small numbers of patients. In a large retrospective hospital‐based cohort study, the authors estimated the risk of a tumor to be masked in a mammogram but visible in an ultrasound examination. Breast density was the strongest predictor for mammography failure, but age, body mass index and previous breast surgery were other factors. The findings could help identify women who should be offered ultrasound additionally to mammography.